Inadequate attitude to the disease as a factor that causes deviation of socialization of personality in patients with psoriasis - Prokopchuk, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the article the features of internal picture of illness are examined in patients with psoriasis as factors which worsen the process of socialization and social adaptation of personality.